2013
DOI: 10.7314/apjcp.2013.14.12.7355
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Common Polymorphisms in MUC1 Gene with H. pylori Infection and Non-cardia Gastric Cancer Risk in a Chinese Population

Abstract: Several lines of evidence support the notion that MUC1 is often aberrantly expressed in gastric cancer, and it is a ligand for Helicobacter pylori. Genetic variation in MUC1 gene may confer susceptibility to H. pylori infection and gastric cancer. We assessed the association of common polymorphisms in MUC1 gene with H. pylori infection and non-cardia gastric cancer using an LD-based tag SNP approach in north-western Chinese Han population. A total of four SNPs were successfully genotyped among 288 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…Studies conducted in Bhutan (Dorji et al, 20013) and China (Zhang et al, 2013) documented identical prevalence with no statistically significance different among age groupd. However, Alizadeh et al (2009) found out that the prevalence of H. pylori increased with age.…”
Section: Discussionmentioning
confidence: 87%
“…Studies conducted in Bhutan (Dorji et al, 20013) and China (Zhang et al, 2013) documented identical prevalence with no statistically significance different among age groupd. However, Alizadeh et al (2009) found out that the prevalence of H. pylori increased with age.…”
Section: Discussionmentioning
confidence: 87%
“…Age and gender distributions were comparable between the two groups. The demographic of subjects are shown in Table 1 (Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Details of the study subjects have been described elsewhere (Zhang et al, 2013). Briefly, all patients with histopathologically confirmed incident non-cardia gastric cancer were consecutively recruited between June 2008 and December 2010 at the cancer hospital of Baotou.…”
Section: Subjectsmentioning
confidence: 99%
“…Again this study recorded higher prevalence of H.pylori in black compared to the white patient. There are conflicting reports on the relationship between age of patients and prevalence of H. pylori, Studies conducted in Bhutan [26] and China [27], documented similar prevalence rate but with no statistically significant difference between H.pylori infection and age group. However, [28] found out that the prevalence of H. pylori increased with age.…”
Section: Discussionmentioning
confidence: 98%